Potenciais efeitos dos dividendos na composição e na performace de fundos de ações no Brasil - Juvercina Sobrinho, Erica (2016)
Like any investment, equity funds are subject to various risks from the fluctuation in the financial conditions of companies and imperfections of the financial market, affecting their performance. However, to classify an asset as a quality investment is subjective and involves strategies based on different attributes. Among the parameters defined in the literature, there is no consensus on the influencing variables in trading assets by mutual funds and, therefore, aimed to analyze the relationship between the distribution of dividends to the profitability of mutual stock funds from 2009 to 2014. If there is something that influences the choice of certain actions to the performance of the funds, the distribution of dividends has been little explored. Through an analysis data due panel using variables outlined by Fama and French (1993, 2015) and Carhart (1997), it was identified that shares in investment funds (on average) use information from dividends to decide on the composition of their portfolios while prioritizing market factor as a marker for decision making. Furthermore, the information provided by the dividend increase appears to be converted to lower performance indicators.